Laboratory Analysis Techniques for the Perinatal Microbiome: Implications for Studies of Probiotic Interventions. Issue 3 (July 2020) - Malloy, Emily; Kates, Ashley; Watson, Lauren; VandeVusse, Leona; Safdar, Nasia; Hanson, Lisa
Abstract : The microbiome is composed of many organisms and is impacted by an intricate exchange between genetics and environmental factors. The perinatal microbiome influences both the developing fetus and the pregnant person. The purpose of this article is to describe the tests that are currently available for laboratory analysis of the perinatal microbiome in relationship to probiotic interventions. This article focuses on the bacterial component of the microbiome. Although adverse outcomes associated with the perinatal microbiome have been studied, a comprehensive understanding of the physiologic perinatal microbiome is still emerging. Early efforts to influence the perinatal microbiome through probiotics are currently under investigation. Unique terminology is defined, and the microbial composition of perinatal microbiota is summarized. The outcomes of studies of antenatal probiotics are summarized. Microbiome testing and analysis are defined and compared. Implications for perinatal care and probiotics research are presented.